Effect of stand density and pruning on growth of ponderosa pines in NW Patagonia, Argentina - Gyenge, Javier Enrique (2010)
Due to the lack of knowledge about ponderosa pine performance under silvopastoral systems (SPS) conditions, the objective of this study was to determine the effect of stand density and pruning on the growth magnitude of ponderosa pines growing in NW Patagonia (SPS with 350 and 500 pines ha−1 vs. commercial densities of 1,300 trees ha−1, HPP). Individual growth rate was higher in SPS 350 trees than in SPS 500 trees, being both higher than in HPP plots, indicating a higher sensitivity of this drought resistance species to relative water availability. The higher individual growth compensated the lower amount of trees per land unit, being the whole stand growth similar or even higher in both SPS treatments than in the HPP stand. Pruning reduced diameter growth in both SPS treatments, at least until 2 years after pruning, with a more marked effect in the pruning treatment with the higher amount of extracted foliage. Carbon fixation reduction in addition to changes in carbon allocation within different plant parts after pruning could be the responsible of observed stem growth reductions. We suggest that higher growth rates in combination with frequent pruning in low density plantations can be applied to shorten the rotation period producing high quality timber in comparison with plantations managed under conventional conditions in Patagonia. Additional advantages could be associated to the lower environmental impact of low canopy cover plantations compared to high density stands.